Under Einstein’s Microscope: Measuring Properties of Individual Rotating Massive Stars from Extragalactic Microcaustic Crossings - Xu Han; Liang Dai (The Astrophysical Journal, 2024)
Highly magnified stars residing in caustic crossing lensed galaxies at z ≃ 0.7–1.5 in galaxy cluster lensing fields inevitably exhibit recurrent brightening events as they traverse a microcaustic network cast down by foreground intracluster stars. The detectable ones belong to nature’s most massive and luminous class of stars, with evolved blue supergiants being the brightest ones at optical wavelengths. Considering single stars in this work, we study to what extent intrinsic stellar parameters are measurable from multifilter light curves, which can be obtained with optical/near-IR space telescopes during one or multiple caustic crossing events. We adopt a realistic model for the axisymmetric surface brightness profiles of rotating O/B stars and develop a numerical lensing code that treats finite source size effects. With a single microcaustic crossing, the ratio of the surface rotation velocity to the breakup value is measurable to a precision of ∼0.1–0.2 for feasible observation parameters with current space telescopes, with all unknown intrinsic and extrinsic parameters marginalized over and without a degeneracy with inclination. Equatorial radius and bolometric luminosity can be measured to 1/3 and 2/3 of the fractional uncertainty in the microcaustic strength, for which the value is not known at each crossing but an informative prior can be obtained from theory. Parameter inference precision may be further improved if multiple caustic crossing events for the same lensed star are jointly analyzed. Our results imply new opportunities to survey individual massive stars in star formation sites at z ≃ 0.7–1.5 or beyond.